Rewriting : how to do things with texts - Harris, Joseph (Joseph D.) (Logan, Utah : Utah State University Press, 2006)
"In Rewriting Joseph Harris draws the college writing student away from static ideas of thesis, support, and structure, and toward a more mature and dynamic understanding. Harris wants college writers to think of intellectual writing as an adaptive and social activity, and he offers them a clear set of strategies - a set of moves - for participating in it." --Book Jacket.
Coming to terms -- Forwarding -- Countering -- Taking an approach -- Revising.
Includes bibliographical references and index.
Keywords: English language -- Rhetoric -- Study and teaching; Persuasion (Rhetoric) -- Study and teaching; Academic writing -- Study and teaching; Academic writing -- Study and teaching; English language -- Rhetoric -- Study and teaching; Persuasion (Rhetoric) -- Study and teaching